Advanced and Intensified Seawater Flue Gas Desulfurization Processes: Recent Developments and Improvements - Nguyen Van Duc Long; Dong Young Lee; Kim Myung Jin; Kwag Choongyong; Lee Young Mok; Lee Sung Won; Moonyong Lee (Energies, 2020)
Seawater flue gas desulfurization (SWFGD) is considered to be a viable solution for coastal and naval applications; however, this process has several drawbacks, including its corrosive absorbent; low vapor loading capacity since the solubility of sulfur oxides (SOx) in seawater is lower than that of limestone used in conventional methods; high seawater flowrate; and large equipment size. This has prompted process industries to search for possible advanced and intensified configurations to enhance the performance of SWFGD processes to attain a higher vapor loading capacity, lower seawater flowrate, and smaller equipment size. This paper presents an overview of new developments as well as advanced and intensified configurations of SWFGD processes via process modifications such as modification and optimization of operating conditions, improvement of spray and vapor distributors, adding internal columns, using square or rectangular shape, using a pre-scrubber, multiple scrubber feed; process integration such as combined treatment of SOx and other gases, and waste heat recovery; and process intensification such as the use of electrified sprays, swirling gas flow, and rotating packed beds. A summary of the industrial applications, engineering issues, environmental impacts, challenges, and perspectives on the research and development of advanced and intensified SWFGD processes is presented.